Female Socio-economic Conditions and Feminization of Poverty in Rural Areas of District Larkana of Sindh, Pakistan - Ghazala Panhwar; B. Faika Tahir; Shabana Tunio, (Progressive Research Journal of Arts & Humanities (PRJAH), 2021)
This paper explores out the relation of feminization of poverty and education as well as the devaluation of the female workforce. Feminization of poverty is a global phenomenon and the prominent in underdeveloped countries. Pakistan does not have any concrete data on the female workforce or feminization of poverty. The ethnological methods were adopted to find out the changes over time. However, such the data acquired through focus group discussion, in-depth interviews, and participant observations. The study aimed to understand the feminization of poverty through the lens of feminism theory. The effect of education was observed. The study shows that the devaluation of female work is more prominent in uneducated female and female-headed households than educated females and male-headed households. The difference between a male and female household and their wage difference was also underpinned in the study. The educated female who was economically independent possessed and heightened confidence level important position in the family as compared to uneducated females. Education had a positive impact on female empowerment and self-awareness. Social norms of rural areas influenced female behaviors towards jobs and earnings. The study examines the everyday life of women in district Larkana. The narrative points out the feminization of poverty and the vicious cycle of poverty in females due to lack of education and low-paying jobs.